Plate Fixation of Expansive Open-Door Laminoplasty Decreases the Incidence of Postoperative C5 Palsy. Issue 4 (May 2019) - Kobayashi, Yoshiomi; Matsumaru, Satoshi; Kuramoto, Tetsuya; Nagoshi, Narihito; Iwanami, Akio; Tsuji, Osahiko; Okada, Eijiro; Fujita, Nobuyuki; Yagi, Mitsuru; Tsuji, Takashi; Ogawa, Jun; Nakamura, Masaya; et al.
Abstract : Study Design: Retrospective study. Objective: To compare outcomes for plate fixation versus suture suspension in expansive open-door laminoplasty (ELAP) for cervical spondylotic myelopathy (CSM). Summary of Background Data: C5 palsy and laminar closure have been reported to occur after ELAP when suture suspension is used to anchor the opened lamina. Materials and Methods: We assessed 174 patients with CSM who were treated by ELAP using either suture suspension (114 patients, mean age 63.3 y, 83 men and 31 women, mean follow-up 12.0 mo) or laminoplasty plate (60 patients, mean age 65.6 y, 45 men and 15 women, mean follow-up 12.6 mo) to maintain the position of the opened laminae. We compared clinical outcomes, radiographic findings, and complications between the 2 groups. Results: Mean Japanese Orthopaedic Association scores had improved significantly for both groups at the final follow-up ( P <0.001), with similar recovery rates: scores improved from 10.8±2.8 to 13.4±2.8 points in the suture-suspension (SS) group and from 11.3±2.7 to 13.6±2.2 points in the laminoplasty plate (LP) group. The incidence of C5 palsy was significantly higher in the SS group (7.9%) than in the LP group (1.7%; P <0.05). Computed tomography (CT) showed larger mean angles of the opened laminae in the SS group compared with the LP group ( P <0.01). Magnetic resonance imaging (MRI) showed that the mean anterior spinal-cord space at the C5 level was larger in the SS group than in the LP group ( P <0.01). Conclusions: Plate fixation in ELAP produced comparable clinical outcomes and significantly lowered the incidence of C5 palsy compared with suture suspension. CT and MRI findings indicated that laminoplasty plate fixation prevented excessive opening of the lamina and decreased dorsal spinal-cord shift, which might explain the lower incidence of C5 palsy.